Сomprehensive Secondary School of Kemerovo During the Great Patriotic War - Alexey V. Blinov (Гуманитарный вектор)
The Great Patriotic War was a test both for the country and for individual regions, localities, organizations and people. Addressing the historical experience is necessary to preserve memory and search for identity. In the modern research projection, aspects of state policy and wartime practices, including the rear regions of the country, have been studied, but there are gaps. Educational practices in the city of Kemerovo, which became the administrative center of the formed region during the war years, the city that was awarded the honorary title of the Russian Federation “City of Labor Valour” in 2021, are poorly studied. In the article, on the basis of historiographical and historical sources, with reliance on general scientific and general historical principles, the theory of “modernization of education” and approaches used in historical and pedagogical research, the tendency of development of general education school of Kemerovo during the Great Patriotic War is shown. The study presents the restored cadre of the heads of the city and district education departments, who were entrusted with solving administrative, organizational, personnel and welfare issues of wartime. The spectrum of priority directions in the work of wartime urban schools aimed, on the one hand, at the implementation of pre-war plans (completion of the fight against illiteracy) and, on the other hand, at finding answers to the challenges of the time (strengthening patriotic education and discipline among students, involvement of urban youth organizations in the educational process, formation of a positive emotional background in the teaching corps, combating homelessness, organization of assistance to the front and home front, etc.) was identified and considered. It has been established that during the Great Patriotic War, thanks to the adoption of balanced decisions, it was possible to preserve the quantitative and improve the qualitative potential of urban schools.